Changes in Oxidant–Antioxidant Status of Hippocampal Tissue Following Eight Weeks of Aerobic Exercise and Vitamin E Supplementation in Reserpine-Induced Parkinsonian Rats - Sadeghi , Fatemeh; Banai, Jamshid; Eftekhari ghinani , Elham; Keshavarz, Saeid (International Journal of Sport Studies for Health, 2025)
Objective: The present study aimed to investigate changes in the oxidant–antioxidant status of hippocampal tissue following eight weeks of aerobic exercise (AT) and vitamin E (VE) supplementation in reserpine-induced Parkinsonian rats.Methods and Materials: In this experimental study, 40 male Sprague-Dawley rats (aged 14–16 months, weighing 250–270 grams) were induced with Parkinson’s disease using 2 mg/kg reserpine (Res) and were divided into the following groups: (1) PD, (2) AT, (3) VE, and (4) AT+VE. To evaluate the effects of Res on the variables, eight healthy control (HC) rats were included. Aerobic exercise was performed for eight weeks, five sessions per week, with each session lasting 15–48 minutes at a speed of 10–24 m/min. VE supplementation was administered orally at a dose of 30 mg/kg daily. Data analysis was performed using one-way ANOVA and Tukey’s post-hoc test (P ≤ 0.05).Findings: The Res+AT, Res+VE, and Res+AT+VE groups showed higher levels of superoxide dismutase (SOD) and total antioxidant capacity (TAC) and lower levels of malondialdehyde (MDA) compared to the Res group (P = 0.05). In the Res+AT+VE group, SOD levels were higher and MDA levels were lower than in the Res+AT and Res+VE groups (P = 0.001). Additionally, TAC levels in the Res+AT and Res+AT+VE groups were higher than in the Res+VE group (P = 0.001).Conclusion: Aerobic exercise and vitamin E supplementation appear to have antioxidant effects on brain tissue, both individually and interactively. Given the more favorable effects of combining exercise with vitamin E, the simultaneous use of these two interventions is recommended in neurodegenerative diseases.